The Development Prospects of Magnetically Levitated Trains - Nikšić, Mladen; Protega, Veselko; Peraković, Dragan (Promet - Traffic&Transportation, 2012)
The paper analyses the up-to-date research in developingmagnetically levitated (MAGLEV) motorcars. It presents thehistorical overview of the development of the most famousmagnetic levitation systems of today.Apart from describing the operation method and the technicalfeatures of each system, the paper ana(vses the advantagesand drawbacks of certain systems, as well as the advantagesand drawbacks of magnetically levitated motorcars comparedto conventional railway.The paper presents the plans for the future as well as the systemswhich have the highest prospects of being also commerciallyand not just experimentally used.